The Relation between Real Estate Business Indicators and Residential Property Price Indices - Nuchachatpong, Arporn; Pinmanee, Pratya; Pattarabanjird, Surachai; Uaviboonsap, Somchai; Lumduan, Adisak (Siam University Journal of Business Administration, 2022)
This paper studies the relation between the growth rate of real estate business indicators and the growth rate of residential property price indices. This study carries out econometric techniques such as unit root test and regression analysis in this topic. Given this, it can be concluded that the growth rate of real estate business indicators cannot explain the growth rate of single-detached house (including land) price index and the growth rate of town house (including land) price index. However, the growth rate of registered housing added (one of real estate business indicators) can explain the growth rate of condominium price index. Moreover, three of real estate business indicators can explain the growth rate of land price index. These are the growth rate of juristic act and right registration fee immovable property, the growth rate of land development licenses nationwide, and the growth rate of requesting a condominium registration nationwide.